Hexagonal Close-Packed 2H-Cu Nanocrystals - Qingbo Wa; An Zhang; Yuhui Tian; Qinbai Yun; Changsheng Chen; Zijian Li; Li Zhai; Gemeng Liang; Biao Huang; Jun Guo; Yao Yao; Qi Yang; et al. (Journal of the American Chemical Society, 2026)
Abstract Tuning the morphology and structure of Cu nanomaterials could effectively regulate their property, functions, and applications. However, it still remains challenging to directly synthesize Cu nanomaterials with an unconventional phase. Here, we report a one-pot wet-chemical synthesis of Cu nanocrystals (NCs) with a hexagonal close-packed (hcp, 2H type) phase, which is different from their thermodynamically stable face-centered cubic (fcc) phase. Compared to the conventional fcc-Cu NCs, the obtained 2H-Cu NCs exhibit enhanced catalytic activity and selectivity in the electrochemical carbon dioxide reduction reaction (CO2RR), achieving a high Faradaic efficiency (FE) of 73.1% toward multicarbon (C2+) products at 600 mA cm–2 under alkaline conditions in a flow cell. Moreover, in situ characterizations and density functional theory (DFT) calculations reveal that the 2H-Cu NCs can optimize the adsorption of the *CO intermediate, leading to a low energy barrier for the formation of C2+ products. This work not only demonstrates an improvement in CO2RR performance of Cu NCs by using the strategy of phase engineering of nanomaterials (PEN) but also opens up an avenue to explore the intrinsic properties and applications of unconventional-phase nanomaterials.